Ground-based measurements of total ozone column amount with a multichannel moderate-bandwidth filter instrument at the Troll research station, Antarctica - Sztipanov, Milos; Tumeh, Lubna; Li, Wei; Svendby, Tove; Kylling, Arve; Dahlback, Arne; Stamnes, Jakob J; Hansen, Georg; Stamnes, Knut (Applied Optics, 2020)
Combining information from several channels of the Norwegian Institute for Air Research (NILU-UV) irradiance meter, one may determine the total ozone column (TOC) amount. A NILU-UV instrument has been deployed and operated on two locations at Troll research station in Jutulsessen, Queen Maud Land, Antarctica, for several years. The method used to determine the TOC amount is presented, and the derived TOC values are compared with those obtained from the Ozone Monitoring Instrument (OMI) located on NASA’s AURA satellite. The findings show that the NILU-UV TOC amounts correlate well with the results of the OMI and that the NILU-UV instruments are suitable for monitoring the long-term change and development of the ozone hole. Because of the large footprint of OMI, NILU-UV is a more suitable instrument for local measurements.
Publisher: OSA
Keywords: Dronning Maud Land; Troll forskningsstasjon; meteorologi; overvåkning; ozonhull; ozonlaget; ultrafiolett stråling